2017
DOI: 10.1186/s12947-017-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the relative contribution of the different right ventricular wall motion components to right ventricular ejection fraction: the ReVISION method

Abstract: Three major mechanisms contribute to right ventricular (RV) pump function: (i) shortening of the longitudinal axis with traction of the tricuspid annulus towards the apex; (ii) inward movement of the RV free wall; (iii) bulging of the interventricular septum into the RV and stretching the free wall over the septum. The relative contribution of the aforementioned mechanisms to RV pump function may change in different pathological conditions.Our aim was to develop a custom method to separately assess the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 35 publications
3
65
0
1
Order By: Relevance
“…It has been shown that 3D echocardiography‐derived ejection fraction is a useful marker of functional status after HTX . Moreover, further analysis of the 3D models enables to separately quantify the different wall motion directions and evaluate the relative contribution of each component . Using this approach, our results confirmed the dominance of radial wall motion in HTX patients.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It has been shown that 3D echocardiography‐derived ejection fraction is a useful marker of functional status after HTX . Moreover, further analysis of the 3D models enables to separately quantify the different wall motion directions and evaluate the relative contribution of each component . Using this approach, our results confirmed the dominance of radial wall motion in HTX patients.…”
Section: Discussionsupporting
confidence: 71%
“…There are three major mechanisms which contribute to RV pump function: (i) longitudinal shortening by traction of the tricuspid annular plane towards the apex; (ii) the inward (radial) motion of the RV free wall referred as the bellows effect; and (iii) the bulging of the interventricular septum during the left ventricular contraction along with stretching the free wall over the septum . The relative significance of the aforementioned mechanisms may be different in certain cardiovascular conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fúj-tató) komponenseinek relatív arányában (26). Ez utóbbi mozgásirány jelentőségét a hagyományos echokardiográfi ás paraméterek gyakorlatilag nem mérik (27), noha teoretikusan akár segítséget jelenthet az edzés indukálta jobbkamra-diszfunkció kimutatásában is.…”
Section: Megbeszélésunclassified
“…10 Measurement of end-systolic RV free wall length relates to the longitudinal contraction of the right ventricle. 11 However, RV contractility does not only depend on the traction of the tricuspid annulus toward the apex. Bulging of the interventricular septum into the RV and radial displacement of the lateral free wall are important contributors to RV pump function.…”
Section: See Article By Amsallem Et Almentioning
confidence: 99%